Holocene Stratigraphy and Geomorphology of Flintstone Hill, Lauder Sandhills, Glacial Lake Hind Basin, Southwestern Manitoba - Running, Garry; Havholm, Karen; Boyd, Matt; Wiseman, Dion (Géographie physique et Quaternaire, 2002)
AbstractSediments exposed at Flintstone Hill in a Souris River cutbank provide the most complete postglacial stratigraphic section in the Glacial Lake Hind Basin (GLHB), southwestern Manitoba. Four lithologic units, A-D, are observed: A1 (~2 m thick), glaciolacustrine silts and clays that grade upward to peat and record final regression of Glacial Lake Hind (~10 500-9300 BP); A2 (~1.5 m thick), low energy fluvial marl and silts grading to O-horizon(s) (by 6700 BP); B (1.5 m thick), dune sands that migrated from the southwest, contrary to the modern wind regime (after ~6700 BP); C (1.0 m thick), thin fluvial deposit between eolian sand sheets (~5500-3200 BP); D (up to 7 m thick), parabolic dune on the modern landscape oriented consistent with the modern wind regime, blowouts suggest episodic dune reactivation (~3200 BP to present). Overall, Flintstone Hill deposits record draining of Glacial Lake Hind, establishment of the Souris River channel through the GLHB, mid-Holocene eolian activity / landscape instability greater than present, and a return to nearly modern conditions by ~5400 BP. Native inhabitants in the GLHB focused on exploiting wetlands and wet meadows before 9300 BP and a landscape similar to the present thereafter.